The Demand for Money in Developing Countries : Assessing the Role of Financial innovation - De Gregorio, Jose.; Arrau, Patricio; Reinhart, Carmen; Wickham, Peter (Washington, D.C. : International Monetary Fund, 1991)
Traditional specifications of money demand have been commonly plagued by persistent overprediction, implausible parameter estimates, and highly autocorrelated errors. This paper argues that some of those problems stem from the failure to account for the impact of financial innovation. We estimate money demand for ten developing countries employing various proxies for the innovation process and provide an assessment of the relative importance of this variable. We find that financial innovation plays an important role in determining money demand and its fluctuations, and that the importance of this role increases with the rate of inflation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet